Human Biodistribution and Radiation Dosimetry of S-11C-Methyl-L-Cysteine Using Whole-Body PET. (October 2015) - Yao, Baoguo; Tang, Caihua; Tang, Ganghua; Hu, Kongzhen; Liang, Xiang; Shi, Xinchong; Nie, Dahong; Tang, Xiaolan; Yue, Dianchao
Abstract : Purpose: S- 11 C-Methyl-L-cysteine ( 11 C-MCYS) is a recently developed amino acid PET tracer for tumor imaging. The present study estimated human radiation absorbed dose of 11 C-MCYS in healthy volunteers based on whole-body PET imaging. Methods: Five sequential whole-body PET scans were performed on 6 healthy volunteers after injection of 11 C-MCYS. Each scan contained of approximately 7 to 10 bed positions, and total scan time of each volunteer was approximately 70 to 85 minutes. Regions of interest were drawn on PET images of source organs. Residence times of 13 source organs for men and 14 source organs for women were calculated from the organ-specific time-activity curves. Absorbed dose estimates were performed from organ residence time by using the medical internal radiation dosimetry method. Results: All volunteers showed initial high uptake in liver, heart, kidneys, pancreas, spleen, and uterus (only women), and followed by rapid clearance. There was very little activity residual in most of the organs except for the liver at the last emission scan time (approximately 75 minutes). The liver was the dose-limiting critical organ with the highest radiation-absorbed dose (1.01E-02 ± 2.64E-03 mGy/MBq), followed by the heart (9.09E-03 ± 1.40E-03 mGy/MBq), and the kidneys (7.12E-03 ± 9.44E-04 mGy/MBq). The effective dose to the whole body was 4.03E-03 ± 1.65E-04 mSv/MBq. A routine injection of 555 MBq (15 mCi) of 11 C-MCYS would lead to an estimated effective dose of 2.24 ± 0.092 mSv. Conclusions: The potential radiation risks associated with 11 C-MCYS PET imaging are within accepted limits. 11 C-MCYS is a safe amino acid PET tracer for tumor imaging and can be used in further clinical studies.